2010
DOI: 10.1111/j.1475-4991.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Approach to Index Numbers for Multilateral Price Comparisons and Their Standard Errors

Abstract: The main objective of the paper is to demonstrate that a number of widely used multilateral index numbers for international comparisons of purchasing power parities (PPPs) and real incomes can be derived using the stochastic approach. The paper shows that price index numbers from commonly used methods like the Ikle, the Rao-weighted and an additive multilateral system are all weighted least squares estimators of the parameters of the country-product-dummy (CPD) model. The advantage of the stochastic approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…The procedures are described in detail in many subsequent papers (e.g. The CPD model has been developed further in the context of PPP estimation, and expressions for computing standard errors of the CPD estimates under alternative stochastic specifications have been derived in Hazargasht and Rao (2010) and in Rao and Hazargasht (2016). The CPD model has been developed further in the context of PPP estimation, and expressions for computing standard errors of the CPD estimates under alternative stochastic specifications have been derived in Hazargasht and Rao (2010) and in Rao and Hazargasht (2016).…”
Section: The Cpd Model and Its Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures are described in detail in many subsequent papers (e.g. The CPD model has been developed further in the context of PPP estimation, and expressions for computing standard errors of the CPD estimates under alternative stochastic specifications have been derived in Hazargasht and Rao (2010) and in Rao and Hazargasht (2016). The CPD model has been developed further in the context of PPP estimation, and expressions for computing standard errors of the CPD estimates under alternative stochastic specifications have been derived in Hazargasht and Rao (2010) and in Rao and Hazargasht (2016).…”
Section: The Cpd Model and Its Extensionmentioning
confidence: 99%
“…Diewert, 2005;Rao, 2005). The CPD model has been developed further in the context of PPP estimation, and expressions for computing standard errors of the CPD estimates under alternative stochastic specifications have been derived in Hazargasht and Rao (2010) and in Rao and Hazargasht (2016).…”
Section: The Cpd Model and Its Extensionmentioning
confidence: 99%
“…The gaps within these vectors, however, are larger than in the grouping approach. To deal with these gaps, we embed our PMO precept into the weighted CPD approach advocated by Rao (2001Rao ( , 2005, Rao (2010), andDiewert (2005). We develop a multi-stage variant of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The quest for indexes with better properties is ongoing and new indexes are being proposed e.g. see Hajargasht & Rao (2010) and Rao & Hajargasht (2016) for a new stochastic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Rao (2005) has shown that the solution to this system can be obtained as weighted least squares estimates from the country-product dummy (CPD) method. Further details of the CPD method and its links with multilateral systems are discussed inHajargasht & Rao (2010) andRao & Hajargasht (2016).…”
mentioning
confidence: 99%